Word Sense Disambiguation on English Translation of Holy Quran - Sarah Abdul-Ameer Mussa; Sabrina Tiun (Bulletin of Electrical Engineering and Informatics, 2015)
This article proposes a system based on the interpretation on the Quranic text that has been translated into English language using word sense disambiguation. This system is based on a combination of three traditional semantic similarity measurements, which are Wu-Palmer (WUP), Lin (LIN), and Jiang-Conrath (JCN) for word sense disambiguation on the English Al-Quran. The experiment was performed to obtain the best overall similarity score. The empirical results demonstrate that the combination of the three mentioned semantic similarity techniques obtained competitive results when compared with using individual similarity measurements.